Operations Management in Measuring the Operational Effectiveness and Efficiency in Company Engaged in Mining Industri - Suhendar, Asep Dadan; Nurmansyah, Andry; Pramuditha, Panji; Santo, Edy (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
One of the mining industry companies that implement operations management to carry out the function of monitoring and controlling production by measuring operational effectiveness and efficiency in the use of heavy equipment is PT Surya Kalimantan Sejati. Understanding how operational management theories and techniques are applied to evaluate and attain production operations' efficacy and efficiency is the goal of this study. Through field observations and interviews with relevant business leaders in the company, this study employs the Action Research Method. By evaluating the efficacy and efficiency of production operations with the necessary ideal production level, the outcomes of applying theories and methodologies in the field of operations management work demonstrate suitability for mining activities.